Building cover crop expertise with citizen science in the upper Midwest: supporting farmer innovation in a time of change - Ingram, Mrill (Frontiers in Sustainable Food Systems, 2023)
The use of cover cropping, as one element in a continuous living cover approach, has the potential to protect water quality and promote soil health, but overall U.S. acreage in cover crops as well as adoption rates remain low. Research on behavioral barriers to cover crop use indicates a lack of information about locally suitable practices and cover crop varieties, as well as the additional management complexity of cover cropping and a high degree of uncertainty in outcomes, especially in areas with shorter growing seasons. This paper describes the development of a citizen science project on cover cropping in Wisconsin designed to (i) generate more geographically distributed data on cover crop performance in the state; and (ii) build understanding of farmer decision-making around growing practices, barriers, and motivations for cover cropping. Citizen science, as it relies on physically distributed members of the public in data generation, is well established as an avenue for generating environmental data. We engage the approach as a tool for also researching influences on individual behavior and identifying potential leverage points for change, especially on-farm innovation and experimentation. I share project findings regarding cover cropping practices and biomass production, results on motivations and influences for cover cropping, as well as participatory approaches to share those results with farmers. This project also offers more general insights into how the citizen science model can be used to expand understanding of decision-making contexts, and to develop responsive outreach efforts that support participants in taking action.